One‐stage, simultaneous skin grafting with artificial dermis and basic fibroblast growth factor successfully improves elasticity with maturation of scar formation. Issue 1 (10th December 2012) - Hamuy, Rodrigo; Kinoshita, Naoshi; Yoshimoto, Hiroshi; Hayashida, Kenji; Houbara, Seiji; Nakashima, Masahiro; Suzuki, Keiji; Mitsutake, Norisato; Mussazhanova, Zhanna; Kashiyama, Kazuya; Hirano, Akiyoshi; Akita, Sadanori
Abstract The efficacy of one‐stage artificial dermis and skin grafting was tested in a nude rat model. Reconstruction with artificial dermis is usually a two‐stage procedure with 2‐ to 3‐week intermission. If one‐stage use of artificial dermis and split‐thickness skin grafting are effective, the overall burden on patients and the medical cost will markedly decrease. The graft take rate, contraction rate, tissue elasticity, histology, morphometric analysis of the dermal thickness, fibroblast counting, immunohistochemistry of α‐smooth muscle actin, matrix metalloproteinase‐2, CD31, and F4/80, as well as gelatin zymography, real‐time reverse transcriptase polymerase chain reaction for matrix metalloproteinase‐2, and electron microscopy, were investigated from day 3 to 3 months postoperatively. The graft take rate was good overall in one‐stage artificial dermis and skin grafting groups up to 3 weeks, and the contraction rate was greater in the two‐staged artificial dermis and skin grafting group than in the skin grafting alone or one stage of artificial dermis and skin grafting groups. Split‐thickness skin grafting with artificial dermis and basic fibroblast growth factor at a concentration of 1 μg/cm2 showed significantly greater elasticity by Cutometer, and the dermal thickness was significantly thinner, fibroblast counting was significantly greater, and the α‐smooth muscle actin expression level was more notable with a more mature blood supply in the dermis and more organized dermal fibrils by electron microscopy at 3 weeks. Thus, one‐stage artificial dermis and split‐thickness skin grafting with basic fibroblast growth factor show a high graft take rate and better tissue elasticity determined by Cutometer analysis, maturity of the dermis, and increased fibroblast number and blood supply compared to a standard two‐stage reconstruction.